Exploring the Role of Family Support and Flexible Working Arrangement in Retaining Grab Drivers: A Fresh Perspective from Malang City - Rifqi, Ahmad; Khan, Ryan Basith Fasih (Universitas Pamulang, 2025)
This study examines the influence of family support and flexible working arrangements on driver retention within the gig economy, specifically focusing on Grab drivers in Malang, Indonesia. A quantitative survey of 400 drivers was conducted to collect data, which was then analyzed using multiple linear regression. Results indicate that family support significantly positively impacts driver retention, providing emotional stability and motivation. While flexible working arrangements alone did not significantly affect retention, they complement family support in fostering work-life balance. These findings contribute to the growing body of research on the gig economy by highlighting the importance of both social and organizational factors in driving employee retention. The study offers practical implications for platform companies seeking to enhance driver satisfaction and reduce turnover.